Designing Molecular Materials Through Thiazyl-Based Radicals - Yutronkie, Nathan (Université d'Ottawa / University of Ottawa, 2020)
Neutral molecular radicals have received increasing attention as building blocks for functional molecular materials owing to their intrinsic conductive and magnetic properties. However, for these systems to be technologically viable, the molecular framework must be capable of stabilizing the unpaired electron, but also enable a degree of control and modulation of the desired properties. To achieve these goals, the design of the radical template requires consideration of the intrinsic effects on the electronic structure and those from a supramolecular perspective. In that regard, thiazyl radicals are promising candidates, as their physical attributes can be tuned systematically for the application at hand. In the pursuit of tunable thiazyl frameworks, two thiatriazinyl radicals have been synthesized and functionalized with heteroaromatic substituents. The contrasting nature between the attached thienyl and pyridyl substituents was evident upon establishing the preparative routes towards the neutral radical, and further demonstrated when the radicals were characterized spectroscopically. Structural analysis has emphasized the ability for the heteroaromatic moieties to direct the assembly of molecules into different supramolecular arrangements, in addition to self-associating into tightly bound structures. While dimerization voids the spin properties of these radicals, the redox-versatile thiatriazinyls were designed to explore the physical properties originating from metal coordination. Using the more robust anionic precursor, a dinuclear dysprosium complex was isolated and structurally analyzed, where oxidation of the ligand occurred in the process. A mechanism towards the self-assembly of the complex has been proposed by NMR studies using the isostructural yttrium analogue, which has provided insights on the metal-ligand reactivity. Furthermore, single-molecule magnet behaviour was observed for the dysprosium complex following magnetic investigations. In contrast to thiatriazinyls, the resonance-stabilized pyridine-bridged bisthiadiazinyls can remain undimerized in the solid state. Three derivatives have been developed with thienyl attachments and vary by the atomic substitution at the basal carbon position (i.e., R = H, F, Cl). Solution measurements illustrated spin delocalization extending across the π-framework, while halogenation provided a handle to fine-tune the energies of frontier molecular orbitals. Moreover, the ability of the thienyl rings to engage in various interactions was manifested in the polymorphic behaviour for each derivative. The solid-state structures were analyzed from single-crystal X-ray diffraction and highlighted the range of supramolecular architectures afforded by these systems. Lastly, two crystallographic phases of a bisdithiazolyl derivative were isolated selectively, such that the low-temperature phase possess an unprecedented high-symmetry trigonal space group. The mix-matched sizes of the beltline substituents afforded a honeycomb arrangement of stacked radicals. Magnetic measurements depicted a transition to an antiferromagnetically ordered state below 8 K, from which a high-temperature series expansion function was developed to model the magnetic data. Analysis of the results suggest the presence of two equivalent spin-spiral sublattices spanning across the crystal lattice three-dimensionally.
Keywords: Neutral Radicals; Thiazyl Chemistry; Molecular Electronics